The Problem of Torture in Italy and its Influence to Potential EU Member States. The case of Macedonia - Jordanoski, Petar (Mediterranean Journal of Social Sciences, 2011)
Human rights, democracy and the rule of law are core values of the EU and are seen as universal and indivisible. Respectfor human rights is a prerequisite for countries seeking to join the Union. Therefore, Macedonia as a candidate country is in the processof fulfilling EU standards in the protection of the human rights. However, huge problem emerges when some of the country members ofthe EU is not respecting and furthermore violates basic human rights of his citizens. As the academic in the country which is supposed tobecome EU member one day, we have huge problem to explain to the people why they should implement some human right standard, ifthat is not the case in some prominent EU member country. Referring to common good and higher values is not always enough. In thispaper will I focus only on two countries: Macedonia and Italy. The first one due the reason is the country where I am living, state intransition trying to reach the European values or at least claiming so. The second one because is one of the oldest EU member states andit’s perceived as one of the most important countries in Europe. Moreover it’s facing with some problem as transition countries do:corruption, freedom of press, fight with mafia, populist leader, illegal immigration and other. I will focus just on the prohibition ontorture as one of the most basic and most fundamental human right.